Insecticides effective against cabbage maggot. Issue 2 (24th May 2016) - Joseph, Shimat Villanassery
Abstract : Cabbage maggot is a serious insect pest of brassica crops such as broccoli and cauliflower in the Central Coast of California. The efficacy of 29 insecticides was determined against cabbage maggot through a laboratory bioassay by exposing field‐collected maggots to insecticide‐treated soil immediately after application. Earn 0.5 CEUs in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/768 .